La codificazione del diritto compromette la sua flessibilità? Il diritto canonico comparato con altri diritti religiosi (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Cento anni di codificazione - 2. Il bisogno di flessibilità - 3. Varietà degli strumenti di flessibilizzazione - 4. I motivi della flessibilità - 5. Necessità - 6. Utilità - 7. Motivi teologici - 8. Flessibilità e codificazione - 9. La codificazione porta all’irrigidimento? - 10. La codificazione agevola i cambiamenti? - 11. Varie funzioni della flessibilizzazione - 12. Piano interpretativo, applicativo o legislativo?Does the Codification of Law affect its Flexibility? The Catholic Canon Law compared to other Religious LawsABSTRACT: Epieikeia in Greek philosophy and aequitas in Roman law are ethical principles, which are open to a religious as well as a secular justification. They are part of the instruments of flexibility that make any legal tradition smooth and adaptable. Jewish and Islamic law as well as Catholic and Orthodox Canon Law apply different kinds of such instruments. A comparison of these legal systems leads to multiple observations: Some scholars, such as Max Weber, considered religious laws to be immutable. In fact, however, they ascribe great significance to flexibility, since they give priority to the spiritual development of individuals. Since many religions are unfamiliar with changes of law by means of legislation, they depend on methods of flexibility to adapt to new social situations. Even those religions, which do have legislation and even codifications, put particular emphasis on instruments of flexibility in order to apply general and abstract norms to individual cases in an appropriate manner.